Perceptions of barriers to the implementation of circular economy initiatives in Central European manufacturing companies - Sebo, Juraj; Gróf, Marek; Kovačič Lukman, Rebeka; Palčič, Iztok; Šebová, Miriam (International Journal of Industrial Engineering and Management, 2025)
This paper examines the relationship between perceived barriers to Circular Economy (CE) initiatives and the specific characteristics of manufacturing companies. The study uses data from a sample of 241 manufacturing companies located in the Central European countries of Slovakia and Slovenia. Data collected as part of the European Manufacturing Survey was analysed with ordered logit regression models to examine the perception of seven commonly mentioned CE barriers. Our results show a significant relationship between the perception of CE barriers in manufacturing companies and their size, nationality, profitability, product/ production characteristics, CE motives and use of CE technologies. Companies with higher profitability were found to be more likely to minimize the significance of CE barriers, while companies with experience of implementing CE technologies (especially remanufacturing) are more likely to perceive most CE barriers. The findings corroborate the conclusions of other studies which have addressed the issue of barriers to innovation. The results can contribute to the creation of better CE policies and practices that consider company-specific features and contextual factors, thereby supporting more effective approach to CE implementation in manufacturing companies. Article history: Received (December 10, 2024); Revised (May 29, 2025); Accepted (June 5, 2025); Published online (August 1, 2025)